Function of the medial meniscus in force transmission and stability. Issue 8 (1st June 2015) - Walker, Peter S.; Arno, Sally; Bell, Christopher; Salvadore, Gaia; Borukhov, Ilya; Oh, Cheongeun
Abstract: We studied the combined role of the medial meniscus in distributing load and providing stability. Ten normal knees were loaded in combinations of compressive and shear loading as the knee was flexed over a full range. A digital camera tracked the motion, from which femoral–tibial contacts were determined by computer modelling. Load transmission was determined from the Tekscan for the anterior horn, central body, posterior horn, and the uncovered cartilage in the centre of the meniscus. For the three types of loading; compression only, compression and anterior shear, compression and posterior shear; between 40% and 80% of the total load was transmitted through the meniscus. The overall average was 58%, the remaining 42% being transmitted through the uncovered cartilage. The anterior horn was loaded only up to 30 degrees flexion, but played a role in controlling anterior femoral displacement. The central body was loaded 10–20% which would provide some restraint to medial femoral subluxation. Overall the posterior horn carried the highest percentage of the shear load, especially after 30 degrees flexion when a posterior shear force was applied, where the meniscus was estimated to carry 50% of the shear force. This study added new insights into meniscal function during weight bearing conditions, particularly its role in early flexion, and in transmitting shear forces.